Characterization of microRNA and mRNA expression profiles in skin tissue between early-feathering and late-feathering chickens - Fang, Guijun; Jia, Xinzheng; Li, Hua; Tan, Shuwen; Nie, Qinghua; Yu, Hui; Yang, Ying (BMC genomics, 2018)
Early feathering and late feathering in chickens are sex-linked phenotypes, which have commercial application in the poultry industry for sexing chicks at hatch and have important impacts on performance traits. However, the genetic mechanism controlling feather development and feathering patterns is unclear. Here, miRNA and mRNA expression profiles in chicken wing skin tissues were analysed through high-throughput transcriptomic sequencing, aiming to understand the biological process of follicle development and the formation of different feathering phenotypes. Compared to the N1 group with no primary feathers extending out, 2893 genes and 31 miRNAs displayed significantly different expression in the F1 group with primary feathers longer than primary-covert feathers, and 1802 genes and 11 miRNAs in the L2 group displayed primary feathers shorter than primary-covert feathers. Only 201 altered genes and 3 altered miRNAs were identified between the N1 and L2 groups (fold change > 2, q value < 0.01). Both sequencing and qPCR tests revealed that PRLR was significantly decreased in the F1 and L2 groups compared to the N1 group, whereas SPEF2 was significantly decreased in the F1 group compared to the N1 or L2 group. Functional analysis revealed that the altered genes or targets of altered miRNAs were involved in multiple biological processes and pathways related to feather growth and development, such as the Wnt signalling pathway, the TGF-beta signalling pathway, the MAPK signalling pathway, epithelial cell differentiation, and limb development. Integrated analysis of miRNA and mRNA showed that 14 pairs of miRNA-mRNA negatively interacted in the process of feather formation. Transcriptomic sequencing of wing skin tissues revealed large changes in F1 vs. N1 and L2 vs. N1, but few changes in F1 vs. L2 for both miRNA and mRNA expression. PRLR might only contribute to follicle development, while SPEF2 was highly related to the growth rate of primary feathers or primary-covert feathers and could be responsible for early and late feather formation. Interactions between miR-1574-5p/NR2F, miR-365-5p/JAK3 and miR-365-5p/CDK6 played important roles in hair or feather formation. In all, our results provide novel evidence to understand the molecular regulation of follicle development and feathering phenotype.